2018
DOI: 10.1177/0022034518811861
|View full text |Cite
|
Sign up to set email alerts
|

The Function and Regulatory Network ofPax9Gene in Palate Development

Abstract: Cleft palate, a common congenital deformity, can arise from disruptions in any stage of palatogenesis, including palatal shelf growth, elevation, adhesion, and fusion. Paired box gene 9 (Pax9) is recognized as a vital regulator of palatogenesis with great relevance to cleft palate in humans and mice. Pax9-deficient murine palatal shelves displayed deficient elongation, postponed elevation, failed contact, and fusion. Pax9 is expressed in epithelium and mesenchyme, exhibiting a dynamic expression pattern that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 71 publications
(149 reference statements)
0
17
0
Order By: Relevance
“…This communication is based on the overlaying of the Fgf9 and Fgfr2 expression patterns in the epithelium of the developing palate and the resultant in modulation of palatal cell proliferation by Fgf9-Fgfr2 (Huang et al, 2016;Weng et al, 2018). Additionally, Fgfr2 combined with Fgf10, which is expressed in the palatal mesenchyme, along with Shh, plays an essential role in EMC (Colvin et al, 2001;Li et al, 2019). Studies have shown that Fgf9 participates in the Shh-Fgfr2-Fgf10 pathway during lung, cecal, and inner ear development (Colvin et al, 2001;Pirvola et al, 2004;Al Alam et al, 2012).…”
Section: Fgf9 Plays An Essential Role In the Epithelial-mesenchymal Cmentioning
confidence: 99%
See 2 more Smart Citations
“…This communication is based on the overlaying of the Fgf9 and Fgfr2 expression patterns in the epithelium of the developing palate and the resultant in modulation of palatal cell proliferation by Fgf9-Fgfr2 (Huang et al, 2016;Weng et al, 2018). Additionally, Fgfr2 combined with Fgf10, which is expressed in the palatal mesenchyme, along with Shh, plays an essential role in EMC (Colvin et al, 2001;Li et al, 2019). Studies have shown that Fgf9 participates in the Shh-Fgfr2-Fgf10 pathway during lung, cecal, and inner ear development (Colvin et al, 2001;Pirvola et al, 2004;Al Alam et al, 2012).…”
Section: Fgf9 Plays An Essential Role In the Epithelial-mesenchymal Cmentioning
confidence: 99%
“…For decades, there was a consensus that cell proliferation is the critical factor that induces palatal growth and that it is a requisite for palatal elevation (Li et al, 2019). However, in recent years continuous research has indicated the possible role of HA accumulation in ECM expansion; HA accumulation is no longer merely an internal force for palatal elevation but has emerged as a potential promoter of tissue expansion during palatal growth (Chiquet et al, 2016;Li et al, 2017;Lan et al, 2019;Yonemitsu et al, 2020).…”
Section: Fgf9-induced Cell Proliferation and Hyaluronic Acid Accumulamentioning
confidence: 99%
See 1 more Smart Citation
“…PAX9 is located on chromosome 14q13.3, consists of five exons, and associated with the formation of the teeth and palate. 57,58 Tooth agenesis and the formation of a cleft palate in PAX9-deficient mice have been reported. 59 Schuffenhauer et al, first reported the role of PAX9 in a patient presented with bilateral CLP.…”
Section: Paired Box Genementioning
confidence: 99%
“…Because of the rapid process, the exact molecular mechanism still remains elusive. 1 5 Several hypotheses about the morphological changes have been considered for decades. Walker and Fraser proposed that the PS rapidly remodeled itself by bulging a new protrusion on the lingual wall and regression at the original tip, and described that the PS reorientation proceeded in a wave-liking manner from posterior to anterior.…”
Section: Introductionmentioning
confidence: 99%